2017
DOI: 10.12659/msm.902901
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Starch Microspheres Transcatheter Arterial Chemoembolization (DSM-TACE) in Intrahepatic Cholangiocellular Carcinoma (ICC): Results from a National Multi-Center Study on Safety and Efficacy

Abstract: BackgroundThe aim of this study was to evaluate the safety and efficacy of DSM (degradable starch microspheres) as an embolic agent in transarterial chemoembolization in the treatment of intrahepatic cholangiocellular carcinoma (ICC).Material/MethodsThis was a national, multi-center observational cohort study on the safety and efficacy of DSM-TACE using mitomycin, gemcitabine, cisplatin, doxorubicin, and carboplatin in palliative treatment of ICC. Recruitment period for the study was from January 2010 to June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…In comparison to our results with TARE, complication rate and gravidity of the complications was higher for RFA. Several studies differing in quality have examined the use of TACE for patients with unresectable ICC [28][29][30]. In the prospective study of Kiefer et al [28] with 62 ICC patients, PR, SD, and PD according to RECIST were reported in 11%, 64%, and 24% of patients, respectively.…”
Section: Treatment Alternativesmentioning
confidence: 99%
“…In comparison to our results with TARE, complication rate and gravidity of the complications was higher for RFA. Several studies differing in quality have examined the use of TACE for patients with unresectable ICC [28][29][30]. In the prospective study of Kiefer et al [28] with 62 ICC patients, PR, SD, and PD according to RECIST were reported in 11%, 64%, and 24% of patients, respectively.…”
Section: Treatment Alternativesmentioning
confidence: 99%
“…Iezzi et al (28,29) treated 40 patients with DSM-TACE who were dismissed or ineligible for Sorafenib with an OS of 11.3 months, a PFS of 6.4 months, and recommended DSM treatment as a safe and effective second-line option. Besides HCC, DSM-TACE was applied successfully in other entities such as intrahepatic cholangiocarcinoma (CCC) and patients with secondary liver malignancies, highlighting this treatment option and the possible combination with chemotherapeutic agents (30,31). TACE in general is associated with fewer AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding safety, no therapy-related deaths occurred in our study, and only 2.5% (1 of 40) of the patients developed liver abscesses after DEB-TACE therapy, which is not a common occurrence. In a previous study, the most common side effects following TACE were abdominal pain, fever, and elevated transaminase levels ( Aliberti, et al, 2008 ; Carter and Martin Ii, 2009 ; Schicho et al, 2017 ). The incidence of side effects is relatively low, and typically no major adverse events occur ( Poggi et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%